PRESUMPTIONS IN LAW: THEORETICAL AND LEGAL ASPECTS - Shvachka, Viktoriia; Dubas, Marharyta (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to investigate the theoretical aspects of presumptions in law by revealing their nature and determining general features; to clarify the existing classifications of presumptions in legal science and to reveal the essence of their types; to clarify the features of their use in civil and criminal law. Research methods: in the process of preparing the article, a system of philosophical, general scientific and special methods was applied. Using the general scientific dialectical method, the content and essence of presumptions were clarified. When determining the place of presumptions in the legal system of Ukraine, a systematic research method was used. When analyzing the classifications of presumptions, a formal-dogmatic method was applied. The special-legal method was used when explaining the content of individual concepts and analyzing the norms of current legislation and judicial practice. Results: it was established that a presumption is a rule-method according to which, without special evidence, but only on the basis of establishing legal facts, an assumption can be made about the presence (absence) of certain legal facts or legal relations. Presumption in a legal context has several essential features that make it an important component of the legal process, including legal nature, binding on the parties, predictability of legal consequences, application in various branches of law. Presumptions in law are important legal instruments that significantly facilitate the application of law and ensure legal stability and legal certainty.